PENINGKATAN KUALITAS NILAI KADAR AIR DAN KADAR ZAT TERBANG PADA SERBUK KARBON AKTIF TEMPURUNG KELAPA DENGAN VARIASI SUHU AKTIVASI - Siti Putri Masyitah; Jumiati, Ety; Sirait, Ratni (POLITALA PRESS, 2023)
This research aims to determine the characteristics of coconut shell activated carbon in powder and granular form using quantitative methods. Making activated carbon consists of preparation, carbonization and activation. Then the physical properties were tested and the analysic. Actived carbon is made through a carbonization stage at a temperature of 400°C for 2 hours and activation at a temperature of 800°C, 900°C, and 1000°C for 1 hour. The parameters used are air content and volatile substance content with active carbon quality requirements based on SNI No. 06-3730-1995. The research results showed that the best quality powdered activated carbon at a temperature of 1000°C with an air content of 6.4% and a volatile matter content of 15.2%